The Effect of the Film Sintas Sailing Soundtrack on Interest in Watching Film and Television Student (Universitas Pendidikan Indonesia, 2024)
This journal discusses the use of soundtracks in films. Backsound is understood as sound in the form of music or instruments commonly encountered throughout a film. From this, the meaning of backsound is certainly very different from that of a film's soundtrack. In this context, backsound is crafted as attractively as possible by production houses. A quantitative methodology is employed to measure the impact of music on viewers of survival films. The sample population consists of drifting enthusiasts in the city of Bandung, with a sample size of 30 individuals. The instrument used in this survey is a rating scale of 1-5. This research reveals that backsound creates a more emotional atmosphere in the hearts of film audiences. The process of creating backsound is also not arbitrary. A music stylist must thoroughly understand the content of the film to ensure that the backsound used truly matches the background music they compose.